Interaksi manusia dalam beragama: Studi multidisiplener tentang peran agama dalam memberikan makna dan tujuan hidup - Nisa’, Khoirotun (Maliki Interdisciplinary Journal, 2024)
Humans in the context of religion have become fundamental research objects in the study of the sociology of religion. This multidisciplinary study explores the role of religion in providing meaning and purpose to human life. This article examines human interaction in practicing religion and how it influences their lives. This study highlights the importance of religion in shaping the mental and spiritual aspects of individuals, giving them direction and purpose. This article also discusses the role of religion in encouraging social cohesion and unity, as well as its function as a source of inspiration for cultural development. The study emphasizes the need to respect the existence of different religions and beliefs. The article concludes that religion plays an important role in human life and should be considered as a source of guidance and inspiration, not as a source of conflict and division.